Muzyka i muzykowanie w pokonywaniu trudności komunikacyjnych i językowych u dzieci z diagnozą autyzmu - Minczakiewicz, Elżbieta Maria (Logopedia Silesiana, 2014)
Music and music playing in defeating communication and linguistic difficulties at autistic children Autism in spite of so many studies and experiments that take in recent years, there remains still the subject of lively discussion. Often, even disputes as to its complex, controversial nature. Numerous studies, which so far are involving many specialists approached much science to know this extraordinary phenomenon. Their results allowed after all, the development of many wellknown and accepted in the world of programs to stimulate the development of children and young people affected by the said disorder. The effectiveness of many methods but still not satisfied enough to satisfy the expectations of parents and teachers. Recent years have indeed resulted in a distinct change for the better, especially in terms of attitudes towards children with a diagnosis of autism, as well as their parents, but it seems to be far too little compared to the needs. This changed not only the attitude of society, but also the position of perceiving education authorities and health educational needs of children with autism. It turns out that children with a diagnosis of autism requires not only an adequate education, but also the systematic treatment multiprofile social support and rehabilitation of rational interaction. Hence, this study attempted to take this topic cognitive. The author makes an attempt to stimulate social development of children with a diagnosis of autism, the fun with singing and music. The results confirmed the validity of the assumptions that children affected by autism can be incorporated into a play activity. They may be interested in movement and music. You can while having fun make contact with them. You can also without difficulty incorporate them into a peer group, and this is their great achievement.